ATP-evoked intracellular Ca2+ transients shape the ionic permeability of human microglia from epileptic temporal cortex - Nicole Piera Palomba; Katiuscia Martinello; Germana Cocozza; Sara Casciato; Addolorata Mascia; Giancarlo Di Gennaro; Roberta Morace; Vincenzo Esposito; Heike Wulff; Cristina Limatola; Sergio Fucile (Journal of Neuroinflammation, 2021)
Abstract Background Intracellular Ca2+ modulates several microglial activities, such as proliferation, migration, phagocytosis, and inflammatory mediator secretion. Extracellular ATP, the levels of which significantly change during epileptic seizures, activates specific receptors leading to an increase of intracellular free Ca2+ concentration ([Ca2+]i). Here, we aimed to functionally characterize human microglia obtained from cortices of subjects with temporal lobe epilepsy, focusing on the Ca2+-mediated response triggered by purinergic signaling. Methods Fura-2 based fluorescence microscopy was used to measure [Ca2+]i in primary cultures of human microglial cells obtained from surgical specimens. The perforated patch-clamp technique, which preserves the cytoplasmic milieu, was used to measure ATP-evoked Ca2+-dependent whole-cell currents. Results In human microglia extracellular ATP evoked [Ca2+]i increases depend on Ca2+ entry from the extracellular space and on Ca2+ mobilization from intracellular compartments. Extracellular ATP also induced a transient fivefold potentiation of the total transmembrane current, which was completely abolished when [Ca2+]i increases were prevented by removing external Ca2+ and using an intracellular Ca2+ chelator. TRAM-34, a selective KCa3.1 blocker, significantly reduced the ATP-induced current potentiation but did not abolish it. The removal of external Cl− in the presence of TRAM-34 further lowered the ATP-evoked effect. A direct comparison between the ATP-evoked mean current potentiation and mean Ca2+ transient amplitude revealed a linear correlation. Treatment of microglial cells with LPS for 48 h did not prevent the ATP-induced Ca2+ mobilization but completely abolished the ATP-mediated current potentiation. The absence of the Ca2+-evoked K+ current led to a less sustained ATP-evoked Ca2+ entry, as shown by the faster Ca2+ transient kinetics observed in LPS-treated microglia. Conclusions Our study confirms a functional role for KCa3.1 channels in human microglia, linking ATP-evoked Ca2+ transients to changes in membrane conductance, with an inflammation-dependent mechanism, and suggests that during brain inflammation the KCa3.1-mediated microglial response to purinergic signaling may be reduced.